2009
DOI: 10.1007/s11033-009-9816-8
|View full text |Cite
|
Sign up to set email alerts
|

Two novel SNPs in the coding region of the bovine PRDM16 gene and its associations with growth traits

Abstract: As a zinc-finger protein, PR domain containing 16 (PRDM16) controls brown fat determination by stimulating brown fat-selective genes expression while suppressing the expression of genes selective for white fat cells, whose mutations were associated with myelodysplastic syndrome (MDS) and leukemogenesis in human and murine model of leukemia. To date, no polymorphisms of PRDM16 gene in bovine had been reported. Herein, PCR-SSCP and DNA sequencing methods were employed to screen the genetic variation within PRDM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Previous studies reported genomic regions associated with ADG on BTA 2, 4–7, 9, 11, 14–20, 22, 23, 26, and 28 [38][52]. The SNPs associated with ADG in the present study (Table 4) were mapped to chromosomes previously linked to ADG, with the exception of rs41629972 located on BTA13.…”
Section: Resultssupporting
confidence: 42%
“…Previous studies reported genomic regions associated with ADG on BTA 2, 4–7, 9, 11, 14–20, 22, 23, 26, and 28 [38][52]. The SNPs associated with ADG in the present study (Table 4) were mapped to chromosomes previously linked to ADG, with the exception of rs41629972 located on BTA13.…”
Section: Resultssupporting
confidence: 42%
“…These results are consistent with those of our previous studies (Wang et al, 2010;Xu et al, 2011). For example, Xu et al (2011) found that at the P7 locus of the paired box 7 gene, only two genotypes occur in CY cattle.…”
Section: Discussionsupporting
confidence: 93%
“…With the F ST , H p and XP-CLR with sliding window approaches, nine genes (PRDM16, ZNF382, ZNF461, ERGIC2, ENSCAFG00000033351, CCDC61, ALDH3A2, ENSCAFG00000011141, and ENSCAFG00000018533) were found to show selection signatures. Among these genes, PRDM16 was reported to be associated with growth traits in some species, such as bovine and chicken (Wang et al, 2010;Wu et al, 2021). It is known that PRDM16 controls a brown fat/skeletal muscle switch (Seale et al, 2008), and it might take a role in the growth of Mame Shiba Inu.…”
Section: Discussionmentioning
confidence: 99%